Vertical variation of oxygen isotope in Bay of Bengal and its relationships with water masses. Issue 12 (3rd December 2013) - Sengupta, S.; Parekh, Anant; Chakraborty, S.; Ravi Kumar, K.; Bose, T.
Abstract : [1] We present here, for the first time, comprehensive depth specific (near surface to 1800 m) oxygen isotope (δ 18 O) data set of 175 water samples collected from 22 different locations in the Bay of Bengal (BoB) during July–August 2009 and December–January 2012–2013. The study is aimed to constrain the water mass parameters using oxygen isotope and salinity. Four water masses are identified on the basis of temperature‐salinity relationship: (a) Bay of Bengal Water (BoBW; 0–50 m), (b) Mixed Zone (MZ; 60–120 m), (c) Indonesian Throughflow (ITF; 200–500 m), and (d) Indian Ocean Deep Water (IDW; 600–1800 m). Our study shows: (1) δ 18 O‐salinity correlation (slope = 0.15 ± 0.01; intercept = −4.58 ± 0.24; r 2 = 0.89; n = 54) for the BoBW is found to be consistent with surface BoB water reported earlier, (2) relatively lower correlation ( r 2 = 0.24; n = 47) in underlying mixed zone suggesting mixing of various water masses, (3) significant linear correlation between δ 18 O and salinity in IDW ( r 2 = 0.70) indicating depleted less saline water from southern hemisphere spread up to 18°N, and (4) vertical profiles at various sampling locations showing a continuous enrichment of δ 18 O (0.6–0.8‰) within top 60–100 m irrespective of their proximity to coastline. In conjunction with a sharp decrease in Δ 14 C data below the same depth zone (60–100 m) as reported earlier, we suggest the δ 18 O value reaches to its acme at a zone of mixing between younger BoBW and relatively older ITF. This preliminary study indicates oxygen isotope and salinity together can be used to identify different water masses in the BoB. Key Points: Depth specific O isotope data first time from BoB d18O and salinity used for water mass classification d18O-S relations useful for paleo-ocean circulation